FAKTOR PENDUKUNG DAN PENGHAMBAT PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 PADA SISWA SDIT AR-RAIHAN BANTUL - Osa Arina Manasikana; Aninditya Sri Nugraeni (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
This study aims to identify and describe the online learning process for teachers during the pandemic, as well as to provide an overview of the factors that encourage and hinder during the online learning process. This research is a qualitative research that is descriptive and tends to use an inductive approach. The place of this research is bound, namely in SDIT Ar-Raihan Bantul, we collect data by interviewing several related teachers. The COVID-19 pandemic has had a significant impact in the world of education, especially in the teaching and learning process. The learning process carried out by the teacher changes, which is usually done directly into learning in the network (online). For the hope of this pandemic in the teaching and learning process, namely the communal awareness between all parties (school offices, families) that this pandemic period is a common problem, so it needs to support and strengthen each other. Keywords: learning, covid-19, online